Knowledge of travel medicine possessed by students of nursing in Podlaskie voivodship — a quantitative study - Damme-Ostapowicz, Katarzyna Van; Krajewska-Kułak, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. According to current data published by the World Tourism Organisation over 150 million travellers visit developing countries every year. For medical professionals, including nurses, it is important to have appropriate knowledge in the field, because their contact with patients setting off on a journey or returning from it are increasingly common. Purpose. To study the level of knowledge of travel medicine possessed by students of nursing in the Podlaskie voivodship. Material and methods. The study was based on a survey using a questionnaire constructed by the authors, on a group of 195 students of nursing at the Medical University in Białystok. Results. The Internet proved to be the most popular source of information for travellers, according to 81.5% of students. The majority of surveyed students (80%) believed that it is necessary to perform some preparatory actions before travelling to tropical countries. 66.7% of students mentioned prophylactic vaccination, but a quarter of them was unable to put forward any principles of prophylaxis before long travel. The majority of surveyed nurses (88.2%) have never participated in the pre-travel education of patients. Over 44% of students have not been convinced about their own skills and knowledge of travel medicine. There was a statistically significant correlation between nursing students’ age (p = 0.0414, p = 0.0310), place of living (p = 0.0305, p = 0.0415), level of education (p = 0.0006, p = 0.0295, p = 0.0372, p = 0.0168, p = 0.0067), professional experience ( p = 0.0473, p = 0.0030, p = 0.0055), position occupied ( p = 0.0460) and their knowledge of travel medicine. Conclusions. 1. The knowledge of travel medicine possessed by students of nursing is insufficient. 2. Students of nursing are interested in broadening their knowledge of travel medicine. 3. There is a statistically significant correlation between students’ age, place of living, level of education, professional experience, position occupied and knowledge of travel medicine. Nursing Topics 2012; 20 (3): 327–337